Differences in Learning Achievement between Major Students History of the Faculty of Social Sciences, Semarang State University Active and Inactive Class of 2008 in Student organizations - Apiwie, Pinky Wohing (Universitas Negeri Semarang, 2017)
This study aimed at finding out if the effect of active students in student organizations on their learning outcomes. This time we have two main problems, namely the activity of students in student organizations and student learning outcomes. The hypothesis taken is that there is no influence between the activity of students in student organizations and student learning outcomes. These results indicate the average GPA of students who are active in student activities of 3.38, a minimum GPA of 3.16 and a maximum GPA of 3.6. while the average GPA of students who were not active in student activities amounted to 3.19 GPA minimum GPA of 2.72 and maximum of 3.43.